The Negative Impact of COVID-19 in HCV, HIV, and HPV Surveillance Programs During the Different Pandemic Waves - Romero-Hernández, Beatriz; Martínez-García, Laura; Rodríguez-Dominguez, Mario; Martínez-Sanz, Javier; Vélez-Díaz-Pallarés, Manuel; Pérez Mies, Belen; Muriel, A.; Gea, Francisco; Pérez-Elías, María Jesús; Galán, Juan Carlos (Frontiers in Public Health, 2022)
Background: The coronavirus disease 2019 (COVID-19) pandemic has been a world-wide stress test for health systems. Two years have elapsed since the description of the first cases of pneumonia of unknown origin. This study quantifies the impact of COVID-19 in the screening program of chronic viral infections such as human papillo-mavirus (HPV), human immunodeficiency virus (HIV) and hepatitis C virus (HCV) along the six different pandemic waves in our population. Each wave had particular epi-demiological, biological, or clinical patterns. Methods: We analyzed the number of samples for screening of these viruses from March 2020 to February 2022, the new infections detected in the pandemic period com-pared to the previous year, the time elapsed between diagnosis and linking to treatment and follow-up of patients, and the percentage of late HIV diagnosis. Moreover, we used the origin of the samples as a marker for quantifying the restoration of activity in prima-ry care. Results: During the first pandemic year, the number of samples received was reduced by 26.7%, 22.6% and 22.5% for molecular detection of HPV or serological HCV and HIV status respectively. The highest decrease was observed during the first wave with 70%, 40% and 26.7% for HPV, HCV and HIV. As expected, new diagnoses also de-creased by 35.4%, 58.2% and 40.5% for HPV, HCV and HIV respectively during the first year of the pandemic. In the second year of the pandemic, the number of samples remained below pre-pandemic period levels for HCV (-3.6%) and HIV (-9.3%) but was slightly higher for HPV (8.0%). The new diag-noses in the second year of the pandemic were of -16.1%, -46.8% and -18.6% for HPV, HCV and HIV respectively. Conclusions: Undoubtedly, an important number of new HPV, HCV and HIV infec-tions were lost during the COVID-19 pandemic, and surveillance programs were dis-rupted as a consequence of collapse of the health system. It is a priority to reinforce these surveillance programs as soon as possible in order to detect undiagnosed cases before the associated morbidity-mortality increases. New pandemic waves could increase the risk of reversing the achievements made over the last few decades.